Situated Environmental Justice: Theorizing Distributional Inequity in Indonesia’s National Strategic Projects (PSN) - Abdul Kodir (Magister Ilmu Administrasi Publik, 2026)
This article develops a situated theorization of Environmental Justice (EJ) grounded in the empirical realities of Indonesia’s National Strategic Projects (Proyek Strategis Nasional/PSN). Drawing on critical policy studies and decolonial scholarship, this study interrogates the limitations of Anglo-American EJ frameworks when applied to developmental state contexts. Through qualitative analysis of PSN governance arrangements, including regulatory frameworks, spatial distribution patterns, and participatory mechanisms, this research identifies three analytical gaps: the assumption of state neutrality, the privileging of technocratic expertise, and the neglect of plural legal orders. The findings reveal that environmental injustice in PSN operates through programmatic rather than project-specific mechanisms, embedded in fast-track regulatory instruments that systematically marginalize affected communities. This article contributes to EJ scholarship by proposing a contextually grounded framework that integrates distributional, procedural, and epistemic dimensions while accounting for the distinctive characteristics of developmental governance in the Global South. The theoretical implications extend beyond Indonesia, offering analytical tools for examining infrastructure-driven development across similar political-economic configurations. Practical recommendations include reforming environmental assessment procedures, strengthening community participation mechanisms, and institutionalizing plural knowledge recognition in project planning.